Pemberdayaan Peserta Didik SMP Sekolah Master Indonesia Depok Dalam Menghadapi Perkembangan Iptek - Ery Setiyawati, Marina; Agustina S.A, Nilla; Calista Dwi, Mayla; Fakhriah, Amalia; Ayu Lativa, Dyah (Universitas Persada Indonesia YAI, 2025)
ABSTRAK Dalam upaya mewujudkan visi